Which of the following is the correct factored form of the given equation?
x 2 - x = 6
(x + 3)(x + 2) = 0
(x + 3)(x - 2) = 0
(x - 3)(x + 2) = 0
(x - 3)(x - 2) = 0

Which of the following is the correct factored form of the given equation?
x 2 - x = 6
(x + 3)(x + 2) = 0
(x + 3)(x - 2) = 0
(x - 3)(x + 2) = 0
(x - 3)(x - 2) = 0

Which of the following is the correct factored form of the given equation? x 2 - x = 6 (x + 3)(x + 2) = 0 (x + 3)(x - 2) = 0 (x - 3)(x + 2) = 0 (x - 3)(x - 2) = 0

Original conversation

User: Which of the following is the correct factored form of the given equation?
x 2 - x = 6
(x + 3)(x + 2) = 0
(x + 3)(x - 2) = 0
(x - 3)(x + 2) = 0
(x - 3)(x - 2) = 0

Weegy: 1/2x^2 - x + 5 = 0 Multiply 2 on both sides: x^2 - 2x + 10 = 0, with coefficient a = 1, b = -2, c = 10 b^2 - 4ac = (-2)^2 - 4(1)(10) = 4 - 40 = - 36 < 0 (there are two complex solutions) x = [2 +/- sqrt (-36)/]/2 = 1 +/- 3i The two solutions are 1 + 3i, 1 - 3i

There are no comments.